ANALISIS PENDAPATAN PASIEN PESERTA JAMINAN KESEHATAN DAERAH (JAMKESDA) DI RUMAH SAKIT UMUM DAERAH dr. ABDUL RIVAI KABUPATEN BERAU - Merlin, Isnaini (ECO-BUILD, 2018)
This research is to find out the level of patients who get Regional Health Insurance (Jamkesda) in RSUD dr. Abdul Rivai, Berau Regency. Based on the results of the study, the sample in this study were 96 Jamkesda patients in dr. Abdul Rivai, Berau Regency. Data processing in this study uses an average average analysis tool and then prints the average income with Eligible (KHL) then to test hypotheses with a 95% confidence level. The results show that the average income of Jamkesda patients in RSUD dr. Abdul Rivai of Berau Regency was Rp. 1,888,542, - Monthly while the Decent Living Needs Value (KHL) of Berau District in 2016 was Rp. 2,778,624, - meaning the income of Jamkesda patients in dr. Abdul Rivai is under the value of Decent Living Needs (KHL). In general, the work of Jamkesda participants in RSUD dr. Abdul Rivai is a farmer, fisherman, daily laborer, builder and housewife whose income is still below the needs of decent living (KHL). Of the 96 respondents there were 10 people from the group of fishermen as many as 7 people, farmers as many as 2 people and builders as many as 1 person whose income was above the needs of Decent Living (KHL), while 86 patients participating participants received income still needed. . Characteristics of patients participating in Jamkesda in dr. Abdul Rivai of Berau District, out of 96 respondents, 89.6% are still classified as poor people who are eligible to become Jamkesda participants.